Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1982
DOI: 10.1055/s-2007-1018995
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Meal Tolerance Test and Reactive Hypoglycemia

Abstract: Twenty-six patients with symptoms suggestive of postprandial hypoglycemia were investigated by oral glucose tolerance test (OGTT). During the OGTT, symptomatic hypoglycemia occurred in 10 (38.5%). Nine of these 10 sugjects were given mixed meal tolerance tests (MMTT) and symptomatic hypoglycemia failed to occur in any case. During the OGTT the nadir glucose was significantly lower than that during MMTT (44.1 +/- 1.5 vs. 77.3 +/- 4.8 mg/dl +/- SEM, respectively; p less than 0.0005). Serum insulin during MMTT pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…Compared to OGTT our breakfast test is markedly more insulinogenic [14], consistent with other authors who have also reported higher insulin responses in breakfast tests compared to OGTT [29]. However, Buss et al [8] and Hogan et al [9] showed similar insulin responses between breakfast and OGTT, and Charles et al [4] a markedly lower response. In this study, we compared our hyperglucidic breakfast with a more classic mixed breakfast which has been designed to be similar to those of Charles et al [4] and Hogan et al [9].…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…Compared to OGTT our breakfast test is markedly more insulinogenic [14], consistent with other authors who have also reported higher insulin responses in breakfast tests compared to OGTT [29]. However, Buss et al [8] and Hogan et al [9] showed similar insulin responses between breakfast and OGTT, and Charles et al [4] a markedly lower response. In this study, we compared our hyperglucidic breakfast with a more classic mixed breakfast which has been designed to be similar to those of Charles et al [4] and Hogan et al [9].…”
Section: Discussionsupporting
confidence: 69%
“…Another question is why this breakfast detected a particular glycaemic pattern in patients with suspected PRH, while breakfasts administered by other authors [4,8,9] did not. Composition of the diverse breakfast tests employed in the literature markedly differs.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations